Sustainable Human Resource Management as A Tool to Build Sustainability - Marzena SYPER-JĘDRZEJAK; Katarzyna WOJTASZCZYK; Izabela ROŻAŃSKA-BIŃCZYK (Communications of International Proceedings, 2023)
This short article aims to prove that there is a need to study sustainable human resource management (HRM). We state that sustainable HRM is necessary to achieve sustainability at the global level. We also show that, despite the development of research on sustainable HRM, this concept is so complex and interdisciplinary that it still requires exploration.
Keywords: sustainable lifestyle; sustainable human resources management; sustainable development